Muscle Glycogen Depletion Following 75-km of Cycling Is Not Linked to Increased Muscle IL-6, IL-8, and MCP-1 mRNA Expression and Protein Content - Nieman, David C.; Zwetsloot, Kevin A.; Lomiwes, Dominic D.; Meaney, Mary P.; Hurst, Roger D. (Frontiers in Physiology, 2016)
The cytokine response to heavy exertion varies widely for unknown reasons, and this study evaluated the relative importance of glycogen depletion, muscle damage, and stress hormone changes on blood and muscle cytokine measures. Cyclists (N=20) participated in a 75-km cycling time trial (168±26.0 min), with blood and vastus lateralis muscle samples collected before and after. Muscle glycogen decreased 77.2±17.4%, muscle IL-6, IL-8, and MCP-1 mRNA increased 18.5±2.8-, 45.3±7.8-, and 8.25±1.75-fold, and muscle IL-6, IL-8, and MCP-1 protein increased 70.5±14.1%, 347±68.1%, and 148±21.3%, respectively (all, P<0.001). Serum myoglobin and cortisol increased 32.1±3.3 to 242±48.3 mg/mL, and 295±27.6 to 784±63.5 nmol/L, respectively (both P<0.001). Plasma IL-6, IL-8, and MCP-1 increased 0.42±0.07 to 18.5±3.8, 4.07±0.37 to 17.0±1.8, and 96.5±3.7 to 240±21.6 pg/mL, respectively (all P<0.001). Increases in muscle IL-6, IL-8, and MCP-1 mRNA were unrelated to any of the outcome measures. Muscle glycogen depletion was related to change in plasma IL-6 (r=0.462, P=0.040), with change in myoglobin related to plasma IL-8 (r=0.582, P=0.007) and plasma MCP-1 (r=0.457, P=0.043), and muscle MCP-1 protein (r=0.588, P=0.017); cortisol was related to plasma IL-8 (r=0.613, P=0.004), muscle IL-8 protein (r=0.681, P=0.004), and plasma MCP-1 (r=0.442, P=0.050). In summary, this study showed that muscle IL-6, IL-8, and MCP-1 mRNA expression after 75-km cycling was unrelated to glycogen depletion and muscle damage, with change in muscle glycogen related to plasma IL-6, and changes in serum myoglobin and cortisol related to the chemotactic cytokines IL-8 and MCP-1.